Preliminary study of short- and long-term outcome and quality of life after minimally invasive surgery for Crohn's disease: Comparison between single incision, robotic-assisted and conventional laparoscopy - Zambonin, Daniela (J Minim Access Surg, 2020)
BACKGROUND: The feasibility of minimally invasive approach for Crohn's disease (CD) is still controversial. However, several meta-analysis and retrospective studies demonstrated the safety and benefits of laparoscopy for CD patients. Laparoscopic surgery can also be considered for complex disease and recurrent disease. The aim of this study was to investigate retrospectively the effect of three minimally invasive techniques on short- and long-term post-operative outcome. PATIENTS AND METHODS: We analysed CD patients underwent minimally invasive surgery in the Digestive Surgery Unit at Careggi University Hospital (from January 2012 to March 2017). Short-term outcome was evaluated with Clavien–Dindo classification and visual analogue scale for post-operative pain. Long-term outcome was evaluated through four questionnaires: Short Form Health Survey (SF-36), Gastrointestinal Quality Of Life Index (GIQLI), Body Image Questionnaire (BIQ) and Hospital Experience Questionnaire (HEQ). RESULTS: There were 89 patients: 63 conventional laparoscopy, 16 single-incision laparoscopic surgery and 10 robotic-assisted laparoscopy (RALS). Serum albumin <30 g/L (P = 0.031) resulted to be a risk factor for post-operative complications. HEQ had a better result for RALS (P = 0.019), while no differences resulted for SF-36, BIQ and GIQLI. CONCLUSIONS: Minimally invasive technique for CD is feasible, even for complicated and recurrent disease. Our study demonstrated low rates of post-operative complications. However, it is a preliminary study with a small sample size. Further studies should be performed to assess the best surgical technique.